Unravelling diversity and metabolic potential of microbial consortia at each stage of leather sewage treatment. Issue 66 (25th August 2017) - Liang, Hebin; Ye, Dongdong; Luo, Lixin
Abstract : Activated sludge is essential for the biological wastewater treatment process and the identification of active microbes enlarges awareness of their ecological functions in this system. Abstract : Activated sludge is essential for the biological wastewater treatment process and the identification of active microbes enlarges awareness of their ecological functions in this system. Microbial communities and their active members were investigated in activated sludge from a leather sewage treatment plant by a combined approach targeting both 16S rRNA and 16S rRNA genes. Although active bacteria obtained by RNA analysis exhibit similar diversity with DNA-based populations, the distribution of microbes significantly differed between the total and active communities. Several active taxa showed low abundance or even absence in the DNA-derived community. Moreover, microbial consortia, particularly bacterial communities, distinctly distributed at a particular treatment stage and both the total and active bacterial communities displayed high environmental sensitivity. Distributions of archaeal communities remained stable and the overrepresentations of active Cenarchaeaceae and Nitrosopumilaceae were potentially associated with ammonia oxidation across the treatment process. Furthermore, bacteria quantitatively dominate the microbial community in activated sludge and the 16S rRNA : 16S rRNA gene ratios of bacteria were positively correlated with the removal of contaminants. The results indicate that both dominant and low-abundance taxa with high potential activity play pivotal roles in removal of contaminants within sewage.